Prevalence of hardcore smoking in the Netherlands between 2001 and 2012: a test of the hardening hypothesis. (December 2016) - Bommelé, Jeroen; Nagelhout, Gera; Kleinjan, Marloes; Schoenmakers, Tim; Willemsen, Marc; van de Mheen, Dike
Abstract Background Hardcore smokers are smokers who have smoked for many years and who do not intend to quit smoking. The "hardening hypothesis" states that light smokers are more likely to quit smoking than heavy smokers (such as hardcore smokers). Therefore, the prevalence of hardcore smoking among smokers would increase over time. If this is true, the smoking population would become harder to reach with tobacco control measures. In this study we tested the hardening hypothesis. Methods We calculated the prevalence of hardcore smoking in the Netherlands from 2001 to 2012. Smokers were 'hardcore' if they a) smoked every day, b) smoked on average 15 cigarettes per day or more, c) had not attempted to quit in the past 12 months, and d) had no intention to quit within 6 months. We used logistic regression models to test whether the prevalence changed over time. We also investigated whether trends differed between educational levels. Results Among smokers, the prevalence of hardcore smoking decreased from 40.8 % in 2001 to 32.2 % in 2012. In the general population, it decreased from 12.2 to 8.2 %. Hardcore smokers were significantly lower educated than non-hardcore smokers. Among the general population, the prevalence of hardcore smoking decreased more among higher educated people than among lower educated people. Conclusions We found no support for the hardening hypothesis in the Netherlands between 2001 and 2012. Instead, the decrease of hardcore smoking among smokers suggests a 'softening' of the smoking population.